2012
DOI: 10.1186/1746-1596-7-12
|View full text |Cite
|
Sign up to set email alerts
|

CD163 versus CD68 in tumor associated macrophages of classical hodgkin lymphoma

Abstract: Classical Hodgkin lymphoma (CHL) is a B-cell lymphoproliferative disorder with a relatively good prognosis. A small but significant percentage of patients, however, will respond poorly to therapy. A recent gene expression profiling study has identified a macrophage signature which has been correlated with primary treatment failure, and immunohistochemical tissue microarray for CD68 was shown to reflect the gene signature as a potentially clinically useful marker to predict adverse prognosis.We examined 44 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 11 publications
6
49
0
2
Order By: Relevance
“…However, these results were not clearly confirmed. 87,88 Harris et al 89 suggested that CD163 staining is superior vs CD68 in the identification of TAMs in neoplastic nodes owing to lower background staining and less nonspecific staining of background inflammatory cells and Hodgkin cells. In addition, Klein et al 90 showed better predictive value using CD163 as a marker of TAMs for survival of cHL patients.…”
Section: Cd68 In Cancermentioning
confidence: 99%
“…However, these results were not clearly confirmed. 87,88 Harris et al 89 suggested that CD163 staining is superior vs CD68 in the identification of TAMs in neoplastic nodes owing to lower background staining and less nonspecific staining of background inflammatory cells and Hodgkin cells. In addition, Klein et al 90 showed better predictive value using CD163 as a marker of TAMs for survival of cHL patients.…”
Section: Cd68 In Cancermentioning
confidence: 99%
“…[10][11][12] However, other studies could not confirm this finding. 13,14 In the present study, we aimed to further characterize the morphologic and immunohistochemical characteristics of HIV-associated Hodgkin lymphoma in comparison to classical Hodgkin lymphoma in non-HIV infected individuals with respect to the composition of the microenvironment and the tumor cell content. The objective of this study was also to evaluate if HIV-associated Hodgkin lymphoma presents a particularly high content of macrophages and if this is related to a 'sarcomatoid' appearance of the infiltrate.…”
mentioning
confidence: 99%
“…The two most promising biomarkers recently under investigation are the interim 2-(1)fluoro-2-deoxy-Dglucose positron emission tomography evaluation after two cycles (PET-2) of chemotherapy 5 and the amount of macrophage infiltrate in the lymphonode at diagnosis, 6,7 but both suffer from a lack of reproducibility in different series. 8 Recently, in this journal, Porrata and colleagues reported that the evaluation of the ALC/AMC-DX ratio, obtained by dividing the absolute lymphocyte count (ALC) over the absolute monocyte count (AMC) from the complete blood count, is an additional independent marker with prognostic value in HL.…”
mentioning
confidence: 99%